2018
DOI: 10.1002/ejoc.201800318
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylations of Simple Acceptors with 2‐O‐Acyl l‐Idose or l‐Iduronic Acid Donors Reveal Only a Minor Role for Neighbouring‐Group Participation

Abstract: Several l‐idose and l‐iduronic acid glycosyl donors (mostly thioglycosides but also halides and trichloroacetimidates) with acyl protecting groups at the C‐2 position were prepared and evaluated in glycosylation reactions with simple acceptors. In glycosaminoglycan oligosaccharide syntheses in the literature, the presence of C‐2 acyl protecting groups in l‐ido‐configured glycosyl donors generally results in exclusive formation of 1,2‐trans glycosidic linkages, a finding that has typically been attributed to ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…By applying this donor, due to the controlling effect of the 4,6‐acetal group, the GH building block was prepared with full 1,2‐ trans ‐α‐stereoselectivity in the absence of a participating group at C2 position. Typically, l ‐idose or l ‐iduronic acid donors with a C2 participating group have been applied for the construction of the α‐ l ‐idosyl glycosidic linkage , . The demonstrated α‐stereodirecting effect of the 4,6‐cyclic acetal in the presence of an ether protecting group at C2 position pave the way to designing new, more diverse protecting group strategies for the synthesis of heparin and heparin sulfate oligosaccharides.…”
Section: Discussionmentioning
confidence: 99%
“…By applying this donor, due to the controlling effect of the 4,6‐acetal group, the GH building block was prepared with full 1,2‐ trans ‐α‐stereoselectivity in the absence of a participating group at C2 position. Typically, l ‐idose or l ‐iduronic acid donors with a C2 participating group have been applied for the construction of the α‐ l ‐idosyl glycosidic linkage , . The demonstrated α‐stereodirecting effect of the 4,6‐cyclic acetal in the presence of an ether protecting group at C2 position pave the way to designing new, more diverse protecting group strategies for the synthesis of heparin and heparin sulfate oligosaccharides.…”
Section: Discussionmentioning
confidence: 99%
“…15b The formation of the anomeric mixture was not surprising as a recent study showed that neighboring-group participation has a minor role for idose donors. 23 Removal of the O-acetyl groups under Zempleń reaction condition followed by 4,6-O-benzylidine protection led to the chromatographically separable mixture of 17 in good yield. The α-anomer 17α was treated with BzCl/Py to furnish the fully protected glycosyl donor 18 (Scheme 3).…”
Section: Synthesis Of Monosaccharide and Disaccharidementioning
confidence: 99%
“…Next, the synthesis of tetrasaccharide trichloroacetimidate donor 3 is summarized in Scheme . Benzoylation of 14 with BzCl, followed by treatment of the resulting 17 with TMSSPh and ZnI 2 , provided the ring‐opened β‐thioglycoside 18 with high stereoselectivity. Selective deprotection of the TBDPS group in 18 afforded diol acceptor 5 .…”
Section: Figurementioning
confidence: 99%